Pengaruh Penguasaan Teori Pengkajian Puisi dan Motivasi Belajar Terhadap Kemampuan Menulis Puisi Pada Siswa Kelas IX SMP Negeri 36 Palembang - Liana Liana (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2016)
The purpose of this study was to determine whether there is the influence of mastering the theory study of poetry, the motivation of the ability to write poetry. The hypotheses are: (1) there is significant relationship between motivation to learn and the ability to write poetry, (2) there is a significant relationship between mastery of the theory of poetry and the ability to write poetry, (3) there is a significant relationship between having motivation to learn, mastery of the theory of poetry the ability to write poetry. The study population was 9th grade students of SMP Negeri 12 Palembang .1. These samples included 40 students. Instrument of this study was a form of objective tests, written tests and questionnaires. The results of this study indicated that there is significant influence between having motivation to learn, mastery of the theory of poetry on the ability to write poetry. The influence was 96.5%. Keywords: having motivation to learn, mastery of the theory of poetry, writing poetry.